(untitled) (Nigerian Journal of Pharmaceutical Research, 2025)
Background and objectives: Pityriasis capitis, commonly known as dandruff, is a prevalent, chronic scalp ailment that affects over half of the world’s population. Dry scalp dandruff is a type of dandruff. Ointments are a good example of a pharmacological formulation that have emollient effects on the scalp and hair. Thus, this study aimed at formulating cosmeceutical herbal ointment as an approach to managing dry scalp dandruff disorder. Methods: Phytochemical screening of Amla (Phyllanthus emblica Linn.) powder and Avocado (Persea americana Mill.) oil was carried out. The ointments were formulated using shea butter as base. Physicochemical, cosmeceutical (conditioning) evaluations, draize skin irritancy test, and stability studies were also carried out. Results: The natural-based ointment formulations, had good organoleptic properties and a pH range of 4.8-7.4. Viscosity was in the range of 20433 to 28007 cp. Spreadability was in the range of 28.49 to 85.24 g.cm/sec. Loss on drying was in the range of 1.77 to 6.73 %. Globule size was in the range of 0.2 – 2.0 µm. The cosmeceutical or conditioning evaluation showed the average score for shine /oiliness, softness and washability to be 2.6 to 4.6, 2.6 to 3.6 and 3.0 respectively. Skin irritancy showed that there was no inflammation, oedema and erythema observed. The formulations exhibited stability in terms of colour, smell, texture and there was no syneresis observed, but there was a difference in the pH of all the formulations. Conclusion: This study has shown that natural based cosmeceutical herbal ointment can be used in managing dry scalp dandruff disorder through its conditioning activities.